The beauty of light in the medieval painting - Arbeláez G., Lucrecia M. (situArte, 2021)
This research aims to establish the most striking features of the metaphysics of light within the aesthetic ideas developed by Christian theologians during the medieval period, especially since the beginning of the Fathers to Scholastica, in order to be represented plastically through various religious artistic manifestations that produced the Catholic Church during the process of consolidation of Christian doctrine through the indoctrination of the populations of Europe and the Americas. The research methodology is based on a documentary design; its basic purpose; its level of depth descriptive and the method used in hermeneutical. The conclusions state that focus on pictorial manifestations of medieval Christian West were characterized by the presence of signs and plastic elements related to light as the gold used in the halos of holy personages.